Inovasi metode pembelajaran mata kuliah filsafat pendidikan islam menggunakan metode painem - Muhlisin, Muzdakir (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2021)
The purpose of this paper is to develop a learning method in the Islamic Education Philosophy Course using the PAINEM method. This study uses a literature review with a descriptive qualitative approach. Learning method is one of the important aspects in realizing the implementation of quality education. The clarity of the learning method is a form of responsibility in carrying out teaching and learning activities so that these activities can be organized and run effectively so that the subject matter can be well received and the learning objectives can be achieved.